Effect of Collagen Types, Bacterial Strains and Storage Duration on the Quality of Probiotic Fermented Sheep’s Milk - Kamil Szopa; Agata Znamirowska-Piotrowska; Katarzyna Szajnar; Małgorzata Pawlos (Molecules, 2022)
Collagen has become popular in dietary supplements, beverages and sports nutrition products. Therefore, the aim of this study was to evaluate the possibility of using various doses of collagen and collagen hydrolysate to produce probiotic sheep’s milk fermented with Lactobacillus acidophilus, Lacticaseibacillus casei, Lacticaseibacillus paracasei and Lacticaseibacillus rhamnosus. The effects of storage time, type and dose of collagen, and different probiotic bacteria on the physicochemical, organoleptic and microbiological properties of fermented sheep’s milk at 1 and 21 days of refrigerated storage were investigated. The addition of collagen to sheep’s milk increased the pH value after fermentation and reduced the lactic acid contents of fermented milk compared to control samples. After fermentation, the number of probiotic bacteria cells was higher than 8 log cfu g−1. In sheep’s milk fermented by L. acidophilus and L. casei, good survival of bacteria during storage was observed, and there was no effect of collagen dose on the growth and survival of both strains. The addition of collagen, both in the form of hydrolysate and bovine collagen, resulted in darkening of the color of the milk and increased the sweet taste intensity of the fermented sheep’s milk. However, the addition of hydrolysate was effective in reducing syneresis in each milk sample compared to its control counterpart.